Marine bivalves as bioindicators for environmental pollutants with focus on dumped munitions in the sea: A review - Strehse, Jennifer S.; Maser, Edmund (Marine environmental research, 2020)
The seas worldwide are threatened by a “new” source of pollution. Munitions dumped into the seas worldwide will corrode and start to leak. Their impacts on the environment and on human health are now more than ever subject of scientific research. Bivalves are a first choice bioindicator and their importance is demonstrated in numerous worldwide studies as well as their integration in important monitoring programs. In this review, the use of mussels in context with marine pollutants in recent years is pointed out in general but with a special focus on dumped conventional and chemical munitions. Monitoring experiments with mussels are able to generate large data sets, which should be mandatory included in decision support tools to increase their weight of evidence. The usefulness of mussels with regard to dumped munitions has clearly been documented in recent years and the further application of this important biomonitoring system is strongly recommended. •Millions of tons of dumped munitions in the seas worldwide corrode and start to leak.•For more than fourty years bivalves have been successfully used as bioindicators.•This review summarises and assesses biomonitoring approaches using bivalves.•Mussel as bioindicator have great potential in the assessment of dumped munitions.